Factors Related to the Success of IVF Program in Morula BMC Clinic Padang - Dewi, Nurmala Sari; Hendri, Dedy; Bachtiar, Hafni (Fakultas Kedokteran Universitas Andalas, 2022)
Introduction: Infertility is the failure of a couple to get pregnant 12 months after having regular sex without contraception. One in seven couples even have to be treated using Assisted Reproductive Technology (TRB). The most widely used TRB is In Vitro Fertilization (IVF). In general, the success rate is in the range of 40-50%. In Indonesia, there are 32 clinics providing IVF program with a success rate of 30-40%. The success rate of IVF is influenced by multi variables that affect directly or indirectly including age, Antral Follicle Count (AFC), Anti Mullerian Hormone (AMH), basal Follicle Stimulating Hormone (FSH), number of egg cells, egg quality, sperm quality, embryo quality, and endometrial thickness. Objectives: This study aims to determine the factors associated with the success of IVF programMethods: This study used a cross-sectional analytic study design which was conducted on 77 medical records of patients undergoing IVF program at Morula Clinic BMC Padang from January 2018-December 2020. All data were then analyzed using univariate, bivariate and multivariate analysis with appropriate statistical test; Results: The average age of the study subjects was (33.4 Â± 3.93) years, the average length of infertility was (6.73 Â± 3.69) years, the most used antagonist protocols (88.16%), with the most common causes of infertility being factors sperm (48.9%) and overweight BMI (36.4%). From the bivariate analysis, it was found that the factors related to the number of eggs were age (r = -0.349), AFC (r = 0.471), FSH (p 0.02), and AMH (p < 0.01) with the dominant factor being AMH. Egg quality was related to AFC (p 0.007) and FSH (p 0.002), with the dominant factor being AFC. Embryo quality correlated with egg quality (p < 0.01). Meanwhile, the success of implantation was dominantly related to the embryo quality factor (0.034); Conclusion: The most dominant factor to the success of IVF program is the quality of the embryo.Keywords: IVF, IVF success